Transient iatrogenic Horner's syndrome following carotid endarterectomy. Issue 2 (22nd February 2019) - Hidayat, Hena; Medani, Mekki; Kavanagh, Eamon
Abstract : We present a case of a 72-year-old man who developed a transient Horner's syndrome in the immediate postoperative period after right carotid endarterectomy which resolved within 3 months. Although Horner's syndrome has been reported with several disorders of the carotid artery, our case documents a rare iatrogenic oculosympathetic paresis after elective carotid endarterectomy.